Soluble Toll-Like Receptors 2 and 4 in Cerebrospinal Fluid of Patients with Acute Hydrocephalus following Aneurysmal Subarachnoid Haemorrhage. - Bartosz Sokół; Norbert Wąsik; Roman Jankowski; Marcin Hołysz; Barbara Więckowska; Paweł Jagodziński (PLoS ONE, 2016)
Background Toll-like receptor (TLR) signalling begins early in subarachnoid haemorrhage (SAH), and plays a key role in inflammation following cerebral aneurysm rupture. Available studies suggest significance of endogenous first-line blockers of a TLR pathway-soluble TLR2 and 4. Methods Eighteen patients with SAH and acute hydrocephalus underwent endovascular coiling and ventriculostomy; sTLR2 and 4 levels were assayed in cerebrospinal fluid (CSF) collected on post-SAH days 0-3, 5, and 10-12. Release kinetics were defined. CSF levels of sTLR2 and 4 were compared with a control group and correlated with the clinical status on admission, the findings on imaging, the degree of systemic inflammation and the outcome following treatment. Results None of study group showed detectable levels of sTLR2 and 4 on post-SAH day 0-3. 13 patients showed increased levels in subsequent samples. In five SAH patients sTLR2 and 4 levels remained undetectable; no distinctive features of this group were found. On post-SAH day 5 the strongest correlation was found between sTLR2 level and haemoglobin level on admission (cc = -0.498, P = 0.037). On post-SAH day 10-12 the strongest correlation was revealed between sTLR2 and treatment outcome (cc = -0.501, P = 0.076). Remaining correlations with treatment outcome, status at admission, imaging findings and inflammatory markers on post-SAH day 5 and 10-12 were negligible or low (-0.5 ≤ cc ≤ 0.5). Conclusions In the majority of cases, rupture of a cerebral aneurysm leads to delayed release of soluble TLR forms into CSF. sTLR2 and 4 seem to have minor role in human post-SAH inflammation due to delayed release kinetics and low levels of these protein.